Prevalence of Coronary Artery Disease and Its Risk Factors in Patients Undergoing Permanent Pacemaker Implantation - Ashwal Adamane Jayaram; Jerry Iype; Deeksha Karkera; Sudhakar M Rao; Tom Devasiya; Padmakumar Ramachandran; Umesh Pai; Jyothi Samanth; Ganesh Paramasivam (International Journal of Cardiovascular Practice, 2019)
Introduction: Some pacemaker implanted patients have an atherosclerotic disease which promotes conduction system ischemia and conduction disturbances. The aim of this study was to determine prevalence of coronary artery disease (CAD) and its risk factors in patients undergoing permanent pacemaker implantation (PPI).Methods: This prospective, single-center hospital based study examined patients older than 40 years who required PPI. Presence of atherosclerotic risk factors and CAD was examined.Results: Of 258 patients undergoing PPI, CAD was present in 50 (19.37 %) patients. CAD was more common among middle age and elderly patients (P = 0.03). Patients older than or equal 76.5 years had specificity of 78.8% for an association with CAD. Multivariate analysis showed that age (odds ratio: 1.042; 95% confidence interval: 1.009–1.075; P = 0.01) and diabetes (odds ratio: 3.437; 95% confidence interval: 1.618–7.303; P = 0.001) had a statistically significant association with CAD. Of 169 patients with involvement of the atrioventricular (AV) node, 28 (16.6 %) had associated left anterior descending artery (LAD) involvement with P = 0.01, suggesting an association between LAD disease and chronic degenerative changes in the AV node.Conclusion: CAD was present in 19.4% of patients undergoing PPI. Age and diabetes had a strong association with CAD. LAD stenosis was significantly more prevalent in AV nodal/ infra-hisian disease compared with sinus nodal disease.